Doomscrolling as a Form of Digital Self-Harm - Svir, Viktoriia; Sevostianov, Pavlo (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The article provides a theoretical analysis of modern domestic and foreign publications on the phenomenon of “doomscrolling”, which is considered not only as a behavioral habit, but also as a potential form of digital self-harm. The goal of our study was to prove that doomscrolling has characteristics that bring it closer to digital self-harm. Based on recent publications, it was proven that doomscrolling – as a form of digital self-harm – has a multifactorial nature. The mechanisms of doomscrolling are described, the main causes, psychological and behavioral consequences of doomscrolling in modern Ukrainians are identified. Practical recommendations are offered for preventing and overcoming doomscrolling. According to the results of the study, it was established that doomscrolling has characteristics that bring it closer to digital self-harm. Doomscrolling is significantly correlated with increased levels of anxiety, depressive symptoms, emotional burnout, and cognitive overstrain. Constant exposure to negative information flows activates stress response mechanisms – increased cortisol levels, emotional instability, sleep disturbances, and decreased concentration. We have proven that doomscrolling is a complex multifactorial phenomenon that combines both psychological and socio-technological components.